A structured review of game coding through modeling - Castro, Diego; Werner, Cláudia Maria Lima (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2021: Anais Estendidos do XX Simpósio Brasileiro de Jogos e Entretenimento DigitalDO - 10.5753/sbgames_estendido.2021.19658, 2021)
Game companies have grown a lot in recent years, reaching billions of dollars a year, despite the game-building process being very complex and time-consuming. This process has evolved considerably over the years. However, it has always been typically characterized by an ad hoc structure with little formal documentation. This lack of structure and documentation can cause severe problems throughout the game's development, such as delivery delays, wrong implementation, maintenance difficulty, among others. One possible solution that can accelerate this development process and increase the level of documentation is the use of modeling for automatic code generation. Based on this, the paper aims to perform a Structured Review to find some information on modeling for game generation, collaborating in game development processes by accelerating coding and assisting with documentation.